Validity and reliability of the 'malay eating assessment tool-10 (M-Eat-10)' among population with neurological disorder in Hospital USM - Leng, Seline Lee Hwei (2018)
The Eating Assessment Tool-1 0 (EAT -1 0) is a validated, quick and easy to selfadminister, symptom-specific outcome tool scale developed by Belasfsky et al. (2008). Currently, the EAT -10 is translated and validated into 10 other languages globally, including the most recent version being the Malay language which was translated and validated by (Farah, 2017. ). The aim for this research is to test the criterion-related validity and internal consistency reliability of the Malay version of Eating Assessment Tool-1 0 (M-EAT -1 0) among population with neurological disorders. Participants were recruited according to the exclusion and inclusion criteria before answering the questionnaire. Eight participants, age ranges from 24 to 65 years old, voluntarily participated in this research. Participants also went through an instrumental assessment of Videofluoroscopic Swallowing Study (VFSS) to validate the presence of dysphagia according to the total scores from the M-EAT-10. By referring to the normative data suggested by Belafsky et al. (2008}, individual with total severity scores of three and above may have dysphagia. The findings of the research found that there is no significant association between the M-EAT-10 and VFSS, tested using Fisher's Exact test (p value= 0.250). The Cronbach's alpha coefficient for Malay version ofEAT-10 (M-EAT-10) obtained was 0.895 (a= 0.895) which indicated good internal consistency of the items in the M-EAT -10 scale. Overall, due to the limited participants affecting the outcome of the research, future research with a larger participant size should be conducted to determine the association between the M-EAT-10 scores with the VFSS. Nevertheless, MEAT -10 can still be used to give early impression and description of patient's symptoms to the clinicians and attending medical doctors in neurology clinics or hospitals in Malaysia.